A Pediatric Case of Acute Pancreatitis as Initial Manifestation of Primary Hyperparathyroidism - Esen, Ihsan; Demir, Fevzi; Deveci, Ugur (Kuwait Medical Assoc, 2016)
The etiology of primary hyperparathyroidism usually involves a single parathyroid adenoma or, less frequently, multiple parathyroid adenomas associated with genetic syndromes. A 14-year-old female patient diagnosed with acute pancreatitis after presenting with vomiting, abdominal pain and waist pain was evaluated. Her physical examination resulted in no relevant findings other than abdominal tenderness. Laboratory investigations yielded the following: calcium: 12.3 mg/dL, phosphate: 2.8 mg/dL, ALP: 368 U/L, PTH: 852 pg/mL, amylase: 1,508 U/L, ALT: 18 U/L, BUN: 30 mg/dL, creatinine: 0.8 mg/dL. Further investigations demonstrated the following: serum 25-OH-D: 5.3 ng/dL, urinary calcium/creatinine ratio: 1.21. Neck ultrasonography was consisted with parathyroid adenoma, sized 2x1 cm, at the posterior side of the thyroid parenchyma of the right thyroid lobe. Scintigraphic examination was reported as the nodular appearance being consistent with parathyroid tissue. Surgical removal was performed on the nodular structure of parathyroid tissue origin. The result of the pathologic investigation of the excised parathyroid nodule was consistent with parathyroid adenoma. An adolescent patient with primary hyperparathyroidism associated with isolated parathyroid adenoma is being presented herein since this is a rare condition in childhood.
Keywords: primary hyperparathyroidism; acute pancreatitis; child